Mineralämnen i fullfoder - Danielsson, Hanna (2005)
In 2003 the recommended phosphorus allowance for dairy cows in Sweden was lowered approximately 10 %. For a cow at a production level of 35 kg ECM it decreased from 0,40 to 0,36 % of dry matter. To investigate if the decrease has been implemented at farm level, analysis of following minerals; P, Ca, Mg, K, Na, S, Se, Cu, Mn and Zn was performed on the TMR at 20 farms in Sweden in the summer of 2004. The purpose was to describe the actual allowance of different minerals as compared to the new recommendations. One hypothesis was that the decrease in recommended allowance of phosphorus would lead to the need of new mineral feeds on the market. Analysis of dry matter and crude protein was also performed to investigate the homogeneity and true recipes of the TMR:s.